Gastrointestinal symptoms among patients with COVID-19 and their relation with co-morbidities - Akhter, Mahfuza; Bhuyia, Rokanuzzaman; Siddique, Md Abu Baker; Hallaz, Mohammad Monsur; Mohammad Nurul Alam, Abul Bashar; Mostafa, Tanvir (BIRDEM Medical Journal, 2023)
Background: Initially, coronavirus disease 2019 (COVID-19) was considered as respiratory disease; later on, it was seen that a large number of patients develop gastro-intestinal (GI) symptoms. Many patients with COVID-19 have underlying co-morbidities. This study was conducted to evaluate the frequency of GI symptoms in COVID-19 patients and to find out its relation with co-morbidities. Methods: This cross-sectional study was done among consecutive COVID-19 positive patients admitted in Mugda Medical College Hospital, Dhaka, Bangladesh from July to September 2020. Information regarding patients’ symptoms and co-morbidities were collected in predesigned structured questionnaire. Results: Among 166 COVID-19 patients, 69% had GI symptoms. Common GI symptoms were anorexia (69%), ageusia (38%), diarrhea (35%) and nausea (31%). Sixty percent patients with GI symptoms had comorbidities; common comorbidities were hypertension (55%) and diabetes mellitus (47%). Comorbidities were more common among patients with GI symptoms (69%) than those without GI symptoms (31%) (p 0.001). Conclusion: This study reflects that over two-thirds of COVID-19 patients developed GI symptoms. More than half of the patients with GI symptoms had co-morbidities. Co-morbidities were common among patients with GI symptoms than non-GI symptoms. BIRDEM Med J 2023; 13(1): 12-15